The wisdom of Nyaaya - Bahadur, Krishna Prakash, 1924- ([Wisdom of India series ; 3], 1978)
Commentary on Gautama's Nyāyasūtra, the aphoristic work setting forth the fundamental considerations of the Nyāya school of Indic philosophy.